Mechanistic investigation and the optimal dose based on baicalin in the treatment of ulcerative colitis–A preclinical systematic review and meta-analysis - Jinchen Chong; Zepeng Chen; Jiaze Ma; Linhai He; Yijia Zhu; Zhihua Lu; Zhengxi Qiu; Chen Chen; Yugen Chen; Feng Jiang (BMC Gastroenterology)
Abstract Background Ulcerative colitis (UC) is a type of inflammatory bowel disease, and current treatments often fall short, necessitating new therapeutic options. Baicalin shows therapeutic promise in UC animal models, but a systematic review is needed. Methods A systematic search was conducted across databases including PubMed, EBSCO, Web of Science, and Science Direct, up to March 2024, identifying randomized controlled trials (RCTs) examining baicalin’s impact on UC in animal models. Seventeen studies were selected through manual screening. Meta-analyses and subgroup analyses utilized Rev Man 5.3 and Stata 15.0 software to assess symptom improvement. Results From 1304 citations, 17 were analyzed. Baicalin significantly modulated various biomarkers: HCS (SMD = -3.91), DAI (MD = -2.75), spleen index (MD = -12.76), MDA (SMD = -3.88), IL-6 (SMD = -10.59), IL-1β (SMD = -3.98), TNF-α (SMD = -8.05), NF-κB (SMD = -5.46), TLR4 (MD = -0.38), RORγ (MD = -0.89), MCP-1 (MD = -153.25), MPO (SMD = -7.34), Caspase-9 (MD = -0.93), Caspase-3 (MD = -0.45), FasL (MD = -1.20)) and enhanced BWC (MD = 0.06), CL (MD = 1.39), ZO-1 (MD = 0.44), SOD (SMD = 3.04), IL-10 mRNA (MD = 3.14), and FOXP3 (MD = 0.45) levels. Baicalin’s actions may involve the PI3K/AKT, TLR4/NF-κB, IKK/IKB, Bcl-2/Bax, Th17/Treg, and TLRs/MyD88 pathways. Optimal therapeutic outcomes were predicted at dosages of 60–150 mg/kg over 10–14 weeks. Conclusion Baicalin demonstrates a multifaceted therapeutic potential in UC, attributed to its anti-inflammatory, antioxidant, anti-apoptotic, and intestinal barrier repair properties. While higher doses and longer treatments appear beneficial, further research, particularly human clinical trials, is necessary to verify its effectiveness and safety in people.